2010
DOI: 10.2478/s11536-009-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of rotaviruses in mid-western Turkey, 2006–2007

Abstract: AbstractVaccines against rotaviruses are now available in numerous countries, including Turkey. As the vaccines may show various efficiencies against different type specificities and routine vaccination in infants might result in selection and immune escape of wild-type rotavirus strains, strain surveillance has been initiated before and during the vaccine introduction. We aimed to provide corresponding information on local strain prevalence in Anatolia, mid-western Turkey duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
2
2
1
Order By: Relevance
“…A study performed on children equal to or less than 5 years old in the Ankara province in Turkey between April 2008 and February 2010 observed G3P[8] predominance with a rate of 38.9% [18] , whereas two other studies on children showed G1[P8] dominancy with the rate of 55.5% and 76% in the same province from September 2004 to June 2006 [19] , [21] . In contrast to previous studies focusing on the dominance of G4P[8] (42.2%) [20] and G2[P4] (47.2%) [43] , we found these genotypes at very low frequencies (3.4% and 6.5%, respectively). In Turkey, the rate of G9P[4] strains increased from 1.6% to 5.6% between September 2004 and December 2005 [19] .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study performed on children equal to or less than 5 years old in the Ankara province in Turkey between April 2008 and February 2010 observed G3P[8] predominance with a rate of 38.9% [18] , whereas two other studies on children showed G1[P8] dominancy with the rate of 55.5% and 76% in the same province from September 2004 to June 2006 [19] , [21] . In contrast to previous studies focusing on the dominance of G4P[8] (42.2%) [20] and G2[P4] (47.2%) [43] , we found these genotypes at very low frequencies (3.4% and 6.5%, respectively). In Turkey, the rate of G9P[4] strains increased from 1.6% to 5.6% between September 2004 and December 2005 [19] .…”
Section: Discussioncontrasting
confidence: 99%
“…A previous study carried out on 119 children from nine provinces in four different regions of Turkey showed that G9P[8] was a less common genotype, with a rate of 3.2% in the period from 2000 to 2002 [20] . However, the increased prevalence of this genotype was observed in two studies from the Ankara province in Turkey between September 2004 and December 2005 (10%) and between January 2008 and January 2009 (19%) [17] , [19] and a multicenter study from four different provinces in Turkey between October 2006 and June 2007 (25%) [43] . The importance of emerging G9P[8] is highlighted by studies in Turkey, but many study groups in different countries have also found a remarkable increase (up to 79%) in the frequency of this genotype [30] , [33] , [44] .…”
Section: Discussionmentioning
confidence: 94%
“…Durmaz et al [4] found the most common genotypes as G9P(8) (40.5%), G1P(8) (21.6%), G2P(8) (9.3%), and G2P(4) (6.5%); these findings were in concordance with our data, with a difference in frequency of G2P(4) (23.0% vs. 6.5%). However, Altindis et al [18] also reported the most frequent genotype as G2P(4) with a frequency rate of 47.2%, the finding that supports the results of our study. Though Cataloluk et al [17] reported the most prevalent genotype as G4P(8) (42.2%), we found only two strains (3.3%) belonging to that particular type.…”
Section: Discussionsupporting
confidence: 92%
“…G3P[8] was the second most common genotype (19.6%) overall, as it predominated in Marmara and South‐East Anatolia and was the second most common genotype in the other regions. Previous studies have shown that the G3P[8] genotype persists in Turkey at a rate of 3.5‐9.6% . Consistent with our data, an Australian rotavirus surveillance study reported that G3P[8] was the second most common genotype, detected in 22.8% of all specimens analyzed in 2015 .…”
Section: Discussionsupporting
confidence: 89%